PRINCIPLE OF “ESTOPPEL”: CONCEPT, FEATURES. CONDITIONS OF APPLICATONS - Пєсцов, Руслан; Гавронська, Тетяна; Горінов, Павло; Деркачова, Наталія; Войтюк, Дарина (SWorldJournal, 2025)
The article is devoted to one of the principles of international law - the principle of “estoppel”, its interpretation and the conditions of its application. The main legal position of the principle of “estoppel” - compliance with the consistency in the b